2014
DOI: 10.1016/j.febslet.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction of miR‐29a by saturated fatty acids impairs insulin signaling and glucose uptake through translational repression of IRS‐1 in myocytes

Abstract: Edited by Laszlo NagyKeywords: MicroRNA miR-29a Palmitate Insulin resistance IRS-1 Saturated fatty acid a b s t r a c t MicroRNAs have been shown to play an important role in insulin signaling but their biological function in insulin resistance induced by saturated fatty acids (SFA) remains largely unknown. Here, we report that SFA palmitate and high fat diet (HFD) significantly increase expression of miR-29a in myocytes. miR-29a targets IRS-1 3'UTR directly and represses IRS-1 expression at the translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 42 publications
3
78
0
Order By: Relevance
“…The knockdown of NLRP3 by RNA interference significantly inhibited insulin resistance which is typically induced in PLIN2-overexpressing C2C12 cells, suggesting that the NLRP3 inflammasome mediates PLIN2-induced insulin resistance. Decreased levels of IRS-1 have been reported to alter insulin signaling in adipocytes and myocytes (24,25). In this study, we observed that IRS-1 expression was decreased in C2C12 cells that overexpressed PLIN2 in the context of insulin exposure, whereas NLRP3 knockdown increased the expression of IRS-1.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The knockdown of NLRP3 by RNA interference significantly inhibited insulin resistance which is typically induced in PLIN2-overexpressing C2C12 cells, suggesting that the NLRP3 inflammasome mediates PLIN2-induced insulin resistance. Decreased levels of IRS-1 have been reported to alter insulin signaling in adipocytes and myocytes (24,25). In this study, we observed that IRS-1 expression was decreased in C2C12 cells that overexpressed PLIN2 in the context of insulin exposure, whereas NLRP3 knockdown increased the expression of IRS-1.…”
Section: Discussionmentioning
confidence: 49%
“…IRS-1, one of the major substrates of the insulin receptor kinase, is essential for the activatation of PI3K in response to insulin, which leads to the phosphorylation of protein kinase B (also known as Akt) and subsequent glucose uptake (23). The downregulation of IRS-1 seems to be the major mechanism involved in the alteration of insulin signaling and glucose transport (24). Thus, we examined the effects of PLIN2 and NLRP3 manipulations on the mRNA expression levels of IRS-1 in the C2C12 cells.…”
Section: Suppression Of Irs-1 By Il-1β Mediates the Effects Of The Nlrp3mentioning
confidence: 99%
“…115,116 Although this remains highly controversial, [117][118][119] host-derived small RNAs are known to regulate many processes of relevance to cardiometabolic risk 120 and to be altered in response to dietary intervention and specific nutrients. 121,122 For example, several microRNAs were reported to be changed in the PBMC transcriptome after 1 year of supplementation with resveratrolcontaining grapeseed extract in subjects with type 2 diabetes mellitus. 123 Thus, the potential functional role of diet acting directly or indirectly through small RNA is intriguing.…”
Section: Noncoding Rnamentioning
confidence: 99%
“…However, it is unclear if and how miR-29a is linked to the regulation of insulin sensitivity in the skeletal muscle. We have found that the expression of miR-29a was up-regulated in the skeletal muscle, liver and serum of HFD-fed mice (60% kcal from fat for 14 weeks) [12] . In addition, the cellular treatment of SFA palmitate in myocytes increased the level of miR-29a expression [12] .…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, the plasma or tissue levels of those miRNAs might be associated with the insulin sensitivity of humans, thereby allowing the development of miRNAs as potential new diagnostic and therapeutic targets in insulin resistance and T2DM [3,5] . Previous our studies unveiled that the certain miRNAs, such as miR-29a and miR-195, were increased in the skeletal muscle and liver of high fat diet (HFD)-fed mice with insulin resistance [12,13] . Hence, we investigated whether these miRNAs could be induced by SFA, and whether these miRNAs might actively participate in SFA-induced insulin resistance.…”
Section: Introductionmentioning
confidence: 94%